Retrorectal cystic hamartoma: A case report of Tailgut Cyst (Research, Society and Development, 2024)
Study design: Case report. Tailgut Cyst (TC) is a congenital retrorectal tumor that arises from remnants of the hindgut during embryonic development, whose symptoms may be nonspecific and treatment consists of complete excision of the cyst, aiming to avoid intra- and postoperative complications.Objective: The objective of this research is to address the case of a patient with Tailgut Cyst and discuss the topic with an emphasis on diagnosis and surgical treatment, analyzing the possible techniques and incisions for the procedure. Methods: The study consists of a specific case of a 56-year-old patient who underwent resection of a retrorectal tumor, later diagnosed by anatomopathologist as Tailgut Cyst, together with an exploratory and descriptive bibliographic analysis, using qualitative methods and approaches. The research participant played a crucial role in providing valuable information about their clinical condition through a structured interview, analyzed and approved by the Ethics Committee.Conclusion: An individualized approach should be recommended for the diagnosis and treatment of CT, with collaboration between different medical specialties. The selection of the surgical technique and outpatient follow-up are crucial to ensure successful results and complete recovery of patients. In summary, the case highlights the complexity of Tailgut Cyst and the need for a comprehensive, interdisciplinary approach to its appropriate management.